1996
DOI: 10.1557/jmr.1996.0111
|View full text |Cite
|
Sign up to set email alerts
|

RF aerosol plasma fabrication of indium tin oxide and tin oxide thin films

Abstract: Transparent, conductive indium-tin oxide (ITO) and tin oxide thin films were deposited on soda-lime-silicate (SLS) float glass and silica glass substrates by an RF aerosol plasma technique in an atmospheric environment. The ITO films were deposited from solutions with various In: Sn ratios. The dependence of the film properties on the substrate temperature, deposition time, and tin concentration has been studied. The films were characterized by several techniques including XRD, EDS, electrical resistivity, SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…These results are in agreement with previous pyrolysis data of other nanometric oxide nanoparticles obtained with starch stabilization [16]. The In 2 O 3 -SnO 2 system is widely studied owing to the commercial application of ITO films [27,28] and its intriguing solid structure [29]. It is well known that the two oxides form a solid solution if the at.% of tin is less than 11% [30,31].…”
Section: Microstructural Characterizationsupporting
confidence: 91%
“…These results are in agreement with previous pyrolysis data of other nanometric oxide nanoparticles obtained with starch stabilization [16]. The In 2 O 3 -SnO 2 system is widely studied owing to the commercial application of ITO films [27,28] and its intriguing solid structure [29]. It is well known that the two oxides form a solid solution if the at.% of tin is less than 11% [30,31].…”
Section: Microstructural Characterizationsupporting
confidence: 91%
“…It was found that the atomic molar percent of indium to tin was determined as 9:1. Generally, when the In:Sn molar ratio is determined as 9:1, ITO nanoparticles have the highest conductivity [5]. According to XRD and EDS data, it was known that ITO nanoparticles with In:Sn = 9:1 (at.…”
Section: Apparatusmentioning
confidence: 99%
“…Indium tin oxide (ITO) films have high visible transmittance, high infrared reflectance, good electrical conductivity, excellent substrate adherence and hardness [3,4]. Those properties have made ITO thin films applied as transparent electrodes for use in liquid crystal display (LCD), plasma display panel (PDP), coating material for use in CRT, transparent conducting thin films, low-emissive windows and solar cells [5]. While several synthesis and processing methods such as sputtering, spray pyrolysis, CVD and dip coating methods have been employed for making thin films of TCOs, research on nanoparticles and quantum dot structures is still quite sparse [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Films with (100) predominant plane were obtained using the atomic layer epitaxy deposition technique [15]. Other researchers [16][17] have noted the preferred orientation of In 2 O 3 crystals toward the (111) or (100) plane, although it did not have any direct effect on reducing film resistivity. Zhu et al [18] used surfactant polyethylene glycol (PEG) to control the morphology of ITO nanorods that present the ratio of length to diameter about 10.…”
Section: Introductionmentioning
confidence: 99%